ANALISIS KOMPARATIF LAPORAN KEBERLANJUTAN PERUSAHAAN PERTAMBANGAN PADA KATEGORI EKONOMI (SERI 200) SESUAI STANDAR GLOBAL REPORTING INITIATIVE - Makherta Sutadji, Ika; Saraswati, Wiwik; Indriastuty, Nina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This research aims to analyze and compare sustainability reports disclosed by mining companies listed on the Indonesia Stock Exchange in the oil and gas production and refinery sub-sector. By using GRI (Global Reporting Initiative) standard guidelines, This research uses the economic category (series 200) as a specific topic focus. The type of research is descriptive-qualitative, with content analysis techniques and comparative methods. The research results show that from the specific topics raised by six companies based on the subsector, six companies were listed. There are 2 companies that, upon accessing the company website, do not report sustainability reports, namely PT. Sugih Energy Tbk SUGI and PT. Super Energy Tbk-SURE. Sustainability Reports were prepared by 4 companies referring to POJK Standards, namely PT. Astrindo Nusantara Infrastruktur Tbk-BIPI, PT. Energi Mega Persada Tbk-ENRG, PT. Medco Energi Internasional Tbk-MEDC, and PT. Mitra Investindo Tbk-MITI. And PT refers to the GRI Standards. Energi Mega Persada Tbk-ENRG and PT. Mitra Investindo Tbk MITI and PT. Medco Energi Internasional Tbk-MEDC. Level of disclosure of specific topics at PT. Mitra Investindo Tbk-MITI by 29% and PT. Energi Mega Persada Tbk-ENRG by 50% and PT. Medco Energi Internasional Tbk-MEDC by 57%. This indicates that there are still many companies that do not refer to the GRI Standards because of their voluntary nature in making sustainability reports. Not all disclosures based on the GRI Standards have been disclosed, so the percentage results are still not high enough. Based on the results of this research, it is hoped that companies can make better and more complete sustainability reports that refer to the GRI Standards in the coming year